A decision support model for individual tree stump harvesting options based on criteria for economic return and environmental protection. Issue 3 (3rd April 2017) - Olsson, Bengt A.; Hannrup, Björn; Jönsson, Mari; Larsolle, Anders; Nordström, Maria; Mörtberg, Ulla; Rudolphi, Jörgen; Strömgren, Monika
ABSTRACT: Based on principles of multi-criteria analysis techniques, a model (MAPStump-E) for decision support on stump harvesting at stand level was developed. The model applies the concept that each stump can be attributed production values (economic) and environmental values (here soil protection and water quality). Individual tree stump information was incorporated directly from the production reports of harvesters and combined with high-resolution Geographical Information System data on topography and soil type to create a production submodel and a soil and water vulnerability submodel (SWM). To test the model, it was applied to a 45-ha study forest in south-central Sweden and the outcome of nine scenarios with varying bioenergy prices and environmental protection levels was examined. Combined analysis of the effects of production and environmental criteria on total dry mass of harvestable stumps at the study site showed that biomass prices had a stronger influence than environmental criteria. Conflict stumps were defined as stumps suitable for harvest based on production criteria, but unsuitable based on soil and water protection criteria. In a "medium" price scenario, the proportion of conflict stumps at the study site ranged from 6% to 18%, depending on protection level set.